Kadirun Yahya: A Perspective from Quranic Studies - Herianto; Zulfi Imran (Alhamdulillah : Jurnal Agama Islam, 2026)
Advancements in science and technology have spurred the emergence of various paradigms seeking to integrate science with spiritual values. One such concept developed in Indonesia is the "metaphysics of technology" proposed by Prof. Dr. H. Kadirun Yahya. While this idea attempts to explain the interconnections between technological phenomena, metaphysical forces, and Islamic teachings, its epistemological foundation requires reconstruction based on the perspective of Qur'anic studies. This research aims to reconstruct the epistemology of Kadirun Yahya’s metaphysics of technology by positioning the Qur'an as the primary source of knowledge and elucidating the relationship between revelation, reason, and empirical experience in the development of knowledge. The study employs a qualitative method utilizing a library research approach. Data were gathered through an examination of Prof. Dr. H. Kadirun Yahya’s works, literature on Qur'anic studies, exegetical texts (tafsir), and relevant scholarly articles, followed by analysis using descriptive-analytical content analysis techniques. The findings indicate that Kadirun Yahya’s epistemology of the metaphysics of technology is characterized by the integration of revelation, reason, and empirical observation; however, it requires methodological refinement to align with the principles of Qur'anic studies. The resulting reconstruction offers an integrative Qur'anic epistemological model that strengthens scientific validity, clarifies knowledge verification mechanisms, and provides a conceptual contribution to the development of Islamic studies and the dialogue between technology, science, and Qur'anic values in the contemporary era.